Optimal cropping pattern for Pothundy canal irrigation project - JISHA L. THOMAS; Sherly M. A; Suhas E. N; Er. Sasikala D (Guide) (Tavanur 2003 Kelappaji College of Agricultural Engineering and Technology)
Optimal cropping pattern for Pothundy canal irrigation project
Optimal cropping pattern for Pothundy canal irrigation project